Endogenous pH, Titratable Acidity and Total Soluble Solid Content of Mouthwashes Available in the Brazilian Market - Cavalcanti, Alessandro Leite; Ramos, Ianny Alves; Leite, Rafaela Bastos; Oliveira, Mariana da Costa; Menezes, Karynna de Melo; Fernandes, Lígia Virgínio; de Castro, Ricardo Dias; Vieira, Fernando Fernandes (European Journal of Dentistry, 2010)
Objectives: To evaluate in vitro the endogenous pH, titratable acidity and total soluble solid content (TSSC) of mouthwashes available in the Brazilian market.Methods: The study sample was composed of 10 commercial brands of mouthwashes based on different active ingredients: Cepacol®, Clinerize®, Equate®, Listerine Cool Citrus®, Oral-B®, Periogard ®, Peroxyl®, Plax Overnight®, Prevident 220® and Sanifill®. The experiments were performed in triplicate. The endogenous pH was evaluated by potentiometry, titratable acidity was evaluated by the addition of 0.1N KOH increments to the mouthwashes, and TSSC readings were performed by Brix refractometry using the Abbé refractometer.Results: pH values ranged from 3.56 (Peroxyl®) to 7.43 (Cepacol®) and three mouthwashes presented pHs below 5.5. The titratable acidity values ranged from 0.007 (Periograd®) to 0.530 (Prevident ®). Oral B® and Clinerize® presented the lowest (4.7%) and the highest (23.70%) TSSC, respectively.Conclusions: Some of the mouthwashes evaluated in this study presented low endogenous pH, even below the critical value for enamel dissolution (pH<5.5), high titratable acidity and high TSSC, and may be potentially erosive to the dental tissues if not properly used. (Eur J Dent 2010;4:156-159)
Keywords: Mouthwashes; Hydrogen-Ion concentration; Dental plaque; Tooth erosion